Characterising the impact of post-treatment storage on chemistry and antimicrobial properties of plasma treated water derived from microwave and DBD sources - Niquet, Rijana; Boehm, Daniela; Schnabel, Uta; Cullen, P.J.; Bourke, Paula; Ehlbeck, Jörg (Wiley-VCH Verlag, 2017)
The biological effects of atmospheric cold plasma generated reactive species are mediated through and at a liquid interface. The diversity of antimicrobial efficacy or intensity of effects may differ with respect to the plasma device or set up, and it is important to understand how these differences occur to advance understanding and successful applications. Thus, plasma treated water (PTW) from a microwave driven plasma source (PTW-MW) and plasma treated water from a di-electric barrier discharge system (PTW-DBD) were compared in terms of long lived reactive species chemical composition and antimicrobial activity. The influence of a post-treatment storage time (PTST), where reactive species in the gas phase were maintained in contact with the liquid was investigated. Nitrogen-based chemistry dominated in PTW-MW, with high concentrations of nitrous acid decomposing to nitrite and nitrate, while H2O2 and nitrate were predominant in PTW-DBD. PTST could enhance H2O2 concentrations in di-electric barrier PTW over time while nitrous acid, the main oxidative species in microwave driven PTW, decreased. This work highlights that plasma treated water presents a resource comprising a range of different compounds, stabilities and reactivities which may be tunable to specific applications.